(untitled) (SCIENCE TIME JOURNAL, 2026)
This article provides a comprehensive comparative analysis of filler units in spontaneous speech in English and Uzbek languages. The study investigates their functional and pragmatic roles, including hesitation management, discourse organization, emotional expression, and interactional control. The research is based on 100 speech samples and applies discourse analysis and statistical methods. The results demonstrate both universal and language-specific characteristics of filler usage.